INVESTIGATING RURAL STUDENTS’ STRATEGIES IN ENGLISH LEARNING - Gani, Sofyan A.; Khairisman, Khairisman; Samad, Iskandar Abdul (International Journal of Education, 2018)
Students’ strategies in learning English attract many EFL researchers’ attention. The objective of this study was to find out rural students’ strategies in English learning. The study was conducted in three different senior high schools in Teunom Sub-District of Aceh Jaya regency. The research used a quantitative method by employing survey design. The modified Strategy Inventory for Language Learning (SILL) questionnaire developed by Oxford was used as an instrument to obtain required data. The population of this survey was all classes in the three schools. Three classes of each school were randomly chosen from the tenth, eleventh, and twelfth grades. Therefore, 136 students of nine classes became the sample of this research. The collected data were analyzed through a quantitative procedure by using a statistical formula to find the percentage of each statement. The results showed that the students employed a variety of strategies in learning English. The most common strategy employed was metacognitive followed by social, affective, memory, cognitive, and compensation.